4D Thermomechanical metamaterials for soft microrobotics - Qingxiang Ji (Nature Portfolio, 2021)
4D metamaterials offer the additional functionality of being responsive to external stimuli. Here, a metamaterial-based soft robot is composed of bilayer plates that can rotate and translate in response to thermal stimuli, allowing controlled motion.